CHARACTERISTICS OF PROFESSIONAL FOREIGN LANGUAGE TEACHING IN HIGHER EDUCATION INSTITUTIONS (Scientific journal of the Fergana State University, 2024)
This article discusses the relevance and importance of foreign language teaching for non-linguistic faculty students. The history of the development of vocationally oriented foreign language teaching is covered. The essence of professional foreign language teaching is defined. Approaches that include the professional-oriented education model, its goals and objectives, problems that arise in the educational process and ways to solve them are presented.